2006
DOI: 10.1016/j.febslet.2006.04.055
|View full text |Cite
|
Sign up to set email alerts
|

The α‐helix of the second chromodomain of the 43 kDa subunit of the chloroplast signal recognition particle facilitates binding to the 54 kDa subunit

Abstract: The a-helix of the second chromodomain of the 43 kDa subunit of the chloroplast signal recognition particle facilitates binding to the 54 kDa subunit Abstract Chloroplasts of higher plants contain a unique signal recognition particle (cpSRP) that consists of two proteins, cpSRP54 and cpSRP43. CpSRP43 is composed of a four ankyrin repeat domain and three functionally distinct chromodomains (CDs). In this report we confirm previously published data that the second chromodomain (CD2) provides the primary binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…2) (27,30). A conserved motif in LHCP, L18, is bound by the Ank repeat region of cpSRP43 (27, 28, 30 -32), and cpSRP54 is bound by CD2 (27,33,34). As expected, these regions are critical for formation of transit complex (Ank1-CD2), LHCP integration (CD1-CD2), and regulation of GTP hydrolysis (CD1) (27).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…2) (27,30). A conserved motif in LHCP, L18, is bound by the Ank repeat region of cpSRP43 (27, 28, 30 -32), and cpSRP54 is bound by CD2 (27,33,34). As expected, these regions are critical for formation of transit complex (Ank1-CD2), LHCP integration (CD1-CD2), and regulation of GTP hydrolysis (CD1) (27).…”
mentioning
confidence: 85%
“…Moreover, only cpSRP43 constructs containing both the Ank repeat domain and CD2 (⌬CD1, ⌬CD3, and Ank1-CD2) were able to replace cpSRP43 in the ability to respond to the addition of Alb3-Cterm. Binding of the Ank repeat domain of cpSRP43 to Alb3-Cterm is likely communicated to cpSRP54/cpFtsY through interaction of the CD2 domain of cpSRP43 with cpSRP54 (33,34,49). It is noteworthy that cpSRP43 constructs lacking CD1 (⌬CD1, His-Ank1-CD2) exhibit elevated levels of GTP hydrolysis in the absence of Alb3-Cterm such that stimulation of GTP hydrolysis by addition of Alb3-Cterm is less pronounced.…”
Section: Cpsrp43 Mediates Alb3 Regulation Of Cpsrpmentioning
confidence: 99%
“…Third, apart from acting as a chaperone, At-cpSRP43 can function as a targeting factor because it is able to interact directly with the translocase Alb3 within the thylakoid membrane (19 -22). In higher plants, the complete pool of stromal cpSRP43 is associated with cpSRP54, forming a stable cpSRP complex (7,8) the subunits of which interact with high affinity as a K d value of 2.5 nM was described for the interaction between At-cpSRP43 and At-cpSRP54M (32). Likewise, the ability of the cpSRP proteins from the moss Physcomitrella to form stable complexes at least in vitro has been recently described (25).…”
Section: Discussionmentioning
confidence: 99%
“…The cpSRP43 Chromodomains Can Bind Alb3 and cpSRP54 Simultaneously-It was previously shown that cpSRP43 CD2 is necessary and sufficient to bind the cpSRP54 M-domain (15,34,35). A stretch of 10 amino acids (RRKR peptide, supplemental Fig.…”
Section: The Alb3-cpsrp43 Interaction Requires Two Positively Chargedmentioning
confidence: 99%